2000
DOI: 10.4049/jimmunol.165.4.2001
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Contribution of T Cell Clonotypes with Public TCR Features to the Chronic Response Against a Dominant EBV-Derived Epitope: Application to Direct Detection of Their Molecular Imprint on the Human Peripheral T Cell Repertoire

Abstract: In an attempt to provide a global picture of the TCR repertoire diversity of a chronic T cell response against a common Ag, we performed an extensive TCR analysis of cells reactive against a dominant HLA-A2-restricted EBV epitope (hereafter referred to as GLC/A2), obtained after sorting PBL or synovial fluid lymphocytes from EBV-seropositive individuals using MHC/peptide multimers. Although TCR β-chain diversity of GLC/A2+ T cells was extensive and varied greatly from one donor to another, we identified in mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
78
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 47 publications
17
78
0
Order By: Relevance
“…However, despite alternative V␤ T cell priming, the immune response to M-MuLV-induced Ags is dominated by the almost exclusive expansion of T cell clones sharing V␤5 gene segments (17). These findings confirm the observations that the massive CD8 ϩ T cell expansion during viral infection (1, 2) in many cases is accompanied by the selection of a V␤ restricted T cell repertoire (7)(8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, despite alternative V␤ T cell priming, the immune response to M-MuLV-induced Ags is dominated by the almost exclusive expansion of T cell clones sharing V␤5 gene segments (17). These findings confirm the observations that the massive CD8 ϩ T cell expansion during viral infection (1, 2) in many cases is accompanied by the selection of a V␤ restricted T cell repertoire (7)(8)(9)(10)(11).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, T cell responses often appear limited to a single encoded immunodominant peptide which generally stimulates a large number of specific CTL, while subdominant epitopes elicit T cell response that do not offer a high protection level against pathogens (5,6). Clonotypic analysis of CD8 T cell response in many cases provides evidence that immunodominant determinants are recognized by a restricted T cell repertoire that uses a limited number of TCRV␤ and/or V␣ domains (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…There is a report describing that chronic antigen stimulation causes limited TCRBV usage and highly conserved CDR3 sequences between distinct individuals, using an MHC/A2-restricted EBV-derived peptide tetramer technique. 34 It has been also demonstrated that CDR3 sequence homology only exists for T cells using the same TCRBV segment. 34 TCRBV segments used by T cell clones in GVHD skin lesions were different between patients UPN01 and UPN02.…”
Section: Discussionmentioning
confidence: 99%
“…The variable degree of diversity of the TCR repertoire observed during chronic virus infections might be related to the experimental strategies used in various studies. Many studies have analyzed the TCR repertoire in T cell lines and/or clones obtained in vitro from a limited number of subjects (21,22) and/or have been based on the use of an incomplete panel of anti-Vb mAbs (14,15,(21)(22)(23), raising the question of to what extent these data were representative of the in vivo situation. With regard to the direct sequencing of the TCR b-chain by anchored PCR in ex vivo Ag-specific sorted cells (19,20,24), it is possible that the TCR repertoire diversity might be underestimated, as the degree of diversity measured will be dependent upon the extent of sequencing with the potential for preferential detection of dominant CD8 T cell clonotypes.…”
mentioning
confidence: 99%